Dilemas e hesitações da modernidade tardia e a emergência da sociedade de controle - Souza, Luís Antônio Francisco de [UNESP] (Universidade Estadual de Londrina, 2010)
The objective of this study is to emphasize the fundamental points of the theoretical discussion about late modernity. In the two last decades, authors like Giddens, Beck, Bauman, Sennett and Garland have emphasized the social, historical and theoretical characterization of modernity in the advanced occidental societies. This discussion, despite being indispensable, does not allow the comprehension of the problems of this new stage of occidental capitalism in terms of its technical dimension and social control. The article arguments in favor of the incorporation of analysis of Michel Foucault’s power and stresses its present reality and potential. This author renewed the theoretical possibilities of the human sciences as he criticized a naturalized view of History and historical events. The influence of his works, an analysis of modernity, may be observed in the debate around the crisis of modernity and the emerging society of control. At the same time, his work helps us understand the main dilemmas and hesitations of contemporary societies.

Pretende-se destacar os pontos fundamentais da discussão teórica sobre modernidade tardia. Autores como Giddens, Beck, Bauman, Sennett e Garland têm se debruçado nas últimas duas décadas sobre a caracterização social, histórica e teórica da modernidade nas sociedades ocidentais avançadas. Esta discussão, embora indispensável, não permite compreender os problemas desta nova etapa do capitalismo ocidental em termos de sua dimensão técnica e de controle social. O artigo argumenta favoravelmente à incorporação da analítica do poder de Michel Foucault e aponta sua atualidade e potencialidades. Este autor renovou as possibilidades teóricas das ciências humanas ao criticar uma visão naturalizada da história e dos acontecimentos históricos. A influência de sua obra, uma analítica da modernidade, pode ser observada no debate em torno da crise da modernidade e da emergência da sociedade de controle. Ao mesmo tempo, seu trabalho ajuda a compreender os principais dilemas e hesitações das sociedades contemporâneas.
Dilemmas and hesitations of late modernity and the emergence of the society of control